Vitamin D3 mediates spatial memory improvement through nitric oxide mechanism in demyelinated hippocampus of rat - Zahra Ataie; Samira Choopani; Forough Foolad; Fariba Khodagholi; Mahdi Goudarzvand (Universidade de São Paulo, 2022)
Abstract Studies have revealed beneficial role of vitamin D3 in neuro-cognitive function. There is also supporting evidence on the involvement of nitric oxide (NO) in the neuro-protective action. However, its over production could contribute to brain disorders. In this study, demyelination was induced by ethidium bromide (EB) injection into the right side of the hippocampus area of male rats. Vitamin D3 was administered to rats for 7 and 28 days prior to behavioral experiments using Morris water maze (MWM). Travelled distance, time spent to reach the platform, and time spent in target zone, were considered for learning and spatial memory evaluation. Nitrite oxide (NO2-) concentration was measured as an indicator for nitric oxide production. The time spent to reach the platform and the travelled distance were decreased significantly by 28 days of vitamin D3 administration (compared to 7 days experiment). Time spent in target quadrant was significantly lowered by administered vitamin on day 28. Therefore, considering a number of studies that have shown the effect of vitamin D3 on cognition, these findings could support their potential effect. Besides, nitric oxide concentration significantly differed in 28 days of vitamin D3 treated group compared with the groups treated with EB or 7 days of vitamin D3.